Apoptosis imaging studies in various animal models using radio-iodinated peptide - Kwak, Wonjung; Ha, Yeong Su; Soni, Nisarg; Lee, Woonghee; Park, Se-Il; Ahn, Heesu; An, Gwang Il; Kim, In-San; Lee, Byung-Heon; Yoo, Jeongsoo (SPRINGER, 2015)
Apoptosis has a role in many medical disorders and treatments; hence, its non-invasive evaluation is one of the most riveting research topics. Currently annexin V is used as gold standard for imaging apoptosis. However, several drawbacks, including high background, slow body clearance, make it a suboptimum marker for apoptosis imaging. In this study, we radiolabeled the recently identified histone H1 targeting peptide (ApoPep-1) and evaluated its potential as a new apoptosis imaging agent in various animal models. ApoPep-1 (CQRPPR) was synthesized, and an extra tyrosine residue was added to its N-terminal end for radiolabeling. This peptide was radiolabeled with I-124 and I-131 and was tested for its serum stability. Surgery- and drug-induced apoptotic rat models were prepared for apoptosis evaluation, and PET imaging was performed. Doxorubicin was used for xenograft tumor treatment in mice, and the induced apoptosis was studied. Tumor metabolism and proliferation were assessed by [F-18]FDG and [F-18]FLT PET imaging and compared with ApoPep-1 after doxorubicin treatment. The peptide was radiolabeled at high purity, and it showed reasonably good stability in serum. Cell death was easily imaged by radiolabeled ApoPep-1 in an ischemia surgery model. And, liver apoptosis was more clearly identified by ApoPep-1 rather than [I-124]annexin V in cycloheximide-treated models. Three doxorubicin doses inhibited tumor growth, which was evaluated by 30-40 % decreases of [F-18]FDG and [F-18]FLT PET uptake in the tumor area. However, ApoPep-1 demonstrated more than 200 % increase in tumor uptake after chemotherapy, while annexin V did not show any meaningful uptake in the tumor compared with the background. Biodistribution data were also in good agreement with the microPET imaging results. All of the experimental data clearly demonstrated high potential of the radiolabeled ApoPep-1 for in vivo apoptosis imaging.
Keywords: TUMOR APOPTOSIS; CANCER; RADIOPHARMACEUTICALS; DESIGN; ANALOG; TOOLS